Good Corporate Governance Effectiveness Mechanism, Special Relationship Transactions, and Leverage on Tax Aggressiveness - Haris Prasetyo Hadi Santoso; Wiwik Utami (International Journal Labs, 2023)
This study examines how effective good corporate governance, control of related party transactions, and leverage are in reducing tax aggressiveness. The research methodology involves cross-sectional and time-series analysis of manufacturing companies listed on the IDX from 2017-2021. Through purposive sampling, 200 observational samples were collected and tested using E-views 12, which produced a random effect model as the best regression model. The findings indicate that good corporate governance with institutional ownership proxies, audit committee activities, and the proportion of independent commissioners did not significantly reduce tax aggressiveness. Leverage with debt-equity ratio proxies also did not demonstrate a significant effect. However, related party transactions had a significant effect in increasing management opportunities to carry out tax aggressiveness. If good corporate governance implementation is not maximized and there is unfairness in related party transactions, it may indicate aggressive tax avoidance.